Primary Health Care 2022
DOI: 10.5772/intechopen.100375
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centred Point-of-Care Testing: A Life-Changing Technology for Remote Primary Care

Abstract: Point-of-care (POC) testing has proven to be a life-changing and transformational technology for patients with acute, chronic, and infectious diseases who live in regional and remote Australia. This technology facilitates patient-centred test results, of equivalent laboratory quality, that are rapidly available to inform clinical and public health decisions with immediate impact on case management. Traditionally, POC testing in high-middle income countries has been most widely used in tertiary or acute care se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Australia has been a pioneer and leader in both the application of POC testing in primary care-particularly services supporting Aboriginal and Torres Strait Islander (now more commonly referred to as First Nations) communities-for the past 25 years. Large-scale POC testing networks (involving close to 100 or more rural and remote First Nations health services) now operate for chronic, acute and infectious diseases across the length and breadth of Australia (Table 1); these are managed for the Australian Government by specialist POC testing network providers including the Flinders University International Centre for Point-of-Care Testing and the Kirby Institute, University of New South Wales, in collaboration with peak First Nations bodies and leadership groups, rather than by traditional pathology laboratories [2,[4][5][6].…”
Section: Poc Testing In Australiamentioning
confidence: 99%
See 2 more Smart Citations
“…Australia has been a pioneer and leader in both the application of POC testing in primary care-particularly services supporting Aboriginal and Torres Strait Islander (now more commonly referred to as First Nations) communities-for the past 25 years. Large-scale POC testing networks (involving close to 100 or more rural and remote First Nations health services) now operate for chronic, acute and infectious diseases across the length and breadth of Australia (Table 1); these are managed for the Australian Government by specialist POC testing network providers including the Flinders University International Centre for Point-of-Care Testing and the Kirby Institute, University of New South Wales, in collaboration with peak First Nations bodies and leadership groups, rather than by traditional pathology laboratories [2,[4][5][6].…”
Section: Poc Testing In Australiamentioning
confidence: 99%
“…The Territory's land mass, Testing, has revolutionised pathology service delivery in the Territory, particularly for acute medical emergencies such as acute myocardial infarction, acute respiratory disorders, acute renal disease and acute blood loss [11,12]. The ability to perform opportunistic tests for cardiac troponin, blood gases, electrolytes and creatinine, and haemoglobin, respectively, have enabled efficient triage of acutely ill patients [13]. The device's international normalised ratio (INR) test also enables the management of patients on warfarin therapy.…”
Section: Poc Testing In Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…The study investigated 200 patient cases with three acute medical presentations at six remote health services: patients with acute chest pain (n = 147), patients with acute diarrhoea (n = 25) and patients with acute exacerbation of renal failure due to a missed dialysis session (n = 21). POC testing enabled more informed triaging of acutely ill patients evacuation to a tertiary hospital as well as ruling out the need for evacuation for patients who could remain in the community and be stabilised [34].…”
Section: The Number Of Patient Tests Performed In the Nt Acute Care P...mentioning
confidence: 99%
“…POC testing networks within remote Australia have demonstrated that when governments have the political will and are prepared to invest in POC testing and required infrastructure then clinical, operational, cultural and economic benefits can be derived for both the patient and healthcare system [5]. This is particularly evident for remote communities and marginalised populations, where access to centralised pathology laboratories is limited and loss to follow-up is high [6].…”
Section: Introductionmentioning
confidence: 99%